Solve the pair of simultaneous equations; (1) y + 4x + 1 = 0, (2) y^2 + 5x^2 + 2x = 0 .

Rearrage equation (1) to make y the subject of the formula. This gives y = -4x -1 .

Substitute this value of y into equation (2). This gives (-4x -1)^2 +5x^2 +2x = 0 . 

Expanding out the brackets gives 16x^2 + 8x + 1 + 5x^2 +2x =0 .

Collecting all the like terms gives 21x^2 +10x + 1 = 0 .

Factorising this equation gives (7x + 1)(3x + 1) = 0 which means x = -1/7, -1/3 . 

Substituting these x values back into (1) implies that y = - 3/7, 1/3 .

Answered by Melanie G. Maths tutor

6286 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Integrate 3x^2 + 4/3 x^5 with respect to x


What is the indefinite integral of cos^2x?


How would you derive y = function of x; for example: y = 3x^3 + x^2 + x


What are the roots of y=x^2+5x+6 ?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences